Effect of hot rolling and annealing on the mechanical properties and thermal conductivity of W-0.5 wt.% TaC alloys. (April 2016) - Miao, S.; Xie, Z.M.; Yang, X.D.; Liu, R.; Gao, R.; Zhang, T.; Wang, X.P.; Fang, Q.F.; Liu, C.S.; Luo, G.N.; Liu, X.; Lian, Y.Y.
Abstract: The mechanical properties and thermal conductivity of W-0.5 wt.% TaC alloys prepared by spark plasma sintering as well as ordinary sintering followed by hot rolling and annealing treatment, respectively, were investigated. Tensile tests indicate that below 600 °C there is no tensile plastic deformation while at 700 °C the total elongation of spark plasma sintered (SPSed) W-0.5 wt.% TaC is up to 36%, which is about 3.3 times that of spark plasma sintered W samples. In contrast, the tensile strength and total elongation of rolled W-0.5 wt.% TaC are 717 MPa and 10.7% at 250 °C, respectively. The ductile-brittle transition temperature (DBTT) of rolled W-0.5 wt.% TaC is between 200 °C and 250 °C, about 300 °C lower than that of spark plasma sintered W-0.5 wt.% TaC ( 600 °C). Annealing decreases the DBTT ( 200 °C) and improves thermal conductivity from 175 to 186 W/m·K at room temperature. Microstructure analyses indicates that TaC could purify and strengthen grain boundaries by capturing impurity oxygen in tungsten to form Ta2 O5 . The results indicate that strength, ductility and thermal conductivity can be improved by purifying, hot rolling and subsequent annealing. Highlights: W-TaC alloys were fabricated by SPS sintering and hot rolling process. The total elongation of the SPSed WTC05 reaches up to 40.0% at 600 °C. The DBTT of rolled WTC05 is between 200 °C and 250 °C. Ta2 O5 particles formed at grain boundaries purify and strengthen GBs.